Cross-Cultural Adjustment: The Role of Cultural Intelligence and Pre-Departure Training - Naufal, Rifqi Ahmad; Sartika, Dina (Yayasan Keluarga Guru Mandiri, 2026)
Every student pursuing studies in a foreign country is highly likely to encounter challenges related to cultural shock, as they must adapt to an environment and regulations that differ from those of their home country. The process of adapting to a cross-cultural environment is critically important for students participating in international exchange programs. This process becomes significantly easier when individuals possess a high level of cultural intelligence and are supported by pre-departure training activities that provide comprehensive information on all necessary preparations for studying abroad. This study employs a quantitative approach, measured through multiple linear regression analysis, by sampling 105 students from Universitas Padjadjaran who participated in the IISMA and IISMAVO programs in 2022. The results of this study indicate that cultural intelligence and pre-departure training have a positive influence on cross-cultural adjustment. This research provides new insights and perspectives in the field of human resource management, particularly in organizational behavior, regarding the relationship between cultural intelligence and pre-departure training on cross-cultural adjustment. It serves as a reference for conducting more in-depth future studies.